2000
DOI: 10.1098/rspa.2000.0522
|View full text |Cite
|
Sign up to set email alerts
|

Linear elastic contact of the Weierstrass profile

Abstract: A contact problem is considered in which an elastic half-plane is pressed against a rigid fractally rough surface, whose pro le is de ned by a Weierstrass series. It is shown that no applied mean pressure is su¯ciently large to ensure full contact and indeed there are not even any contact areas of nite dimension|the contact area consists of a set of fractal character for all values of the geometric and loading parameters.A solution for the partial contact of a sinusoidal surface is used to develop a relation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
176
3
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(182 citation statements)
references
References 20 publications
2
176
3
1
Order By: Relevance
“…Most surfaces are rough enough that atoms are only close enough to interact strongly in areas where peaks or asperities on opposing surfaces overlap. Experiments [1,2,3,4] and theory [5,6,7,8,9,10,11,12] show that this real area of contact A is often much smaller than the projected area A 0 of the surfaces. They have also correlated [1,2,3] the increase in friction with normal load W to a corresponding increase in A.…”
Section: Introductionmentioning
confidence: 99%
“…Most surfaces are rough enough that atoms are only close enough to interact strongly in areas where peaks or asperities on opposing surfaces overlap. Experiments [1,2,3,4] and theory [5,6,7,8,9,10,11,12] show that this real area of contact A is often much smaller than the projected area A 0 of the surfaces. They have also correlated [1,2,3] the increase in friction with normal load W to a corresponding increase in A.…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by the recent work in [3], we have carried out an elastic-plastic contact analysis of a fractal rough surface, which is idealized with a Weierstrass series. Scaling relations of the total contact area versus the applied load and roughness properties can be deduced [4], and compared with numerical simulations that have pre-specified spatial cutoff sizes [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to solve the paradoxes of Ciavarella et al [4], Gao et al [19] added plasticity in the Weierstrass model. While the elastic model [4] showed that the -fractal limit‖ consists of an infinite number of contact spots, with zero size, subjected to infinite contact pressure, Gao et al [19]'s model found that while the total contact area and contact pressure are well defined, it remains impossible to predict the actual number of contacts or their size. They also suggest to add adhesion (but the problem with both plasticity and adhesion has not even been attempted yet) or truncating the fractal process where the fractal description breaks down.…”
Section: Plasticity Modelsmentioning
confidence: 99%
“…In fact, he even anticipated -fractals‖ which were much later used in a more refined form in the -contact sport‖ of rough surfaces. Yet it was only much later that Ciavarella et al [4] remarked that linearity involves a linear coefficient which is scale-dependent, and in particular it goes to zero for realistic fractal geometry. This was done with the not very popular choice of a Weierstrass series as a fractal, but later Gaussian model theories [5] did not change the basic conclusion that -no applied mean pressure is sufficiently large to ensure full contact and indeed there are not even any contact areas of finite dimension -the contact area consists of a set of fractal character for all values of the geometric and loading parameters‖.…”
Section: Introductionmentioning
confidence: 99%